Age, period, cohort trends of suicide in Japan and Korea (1986–2015): A tale of two countries. (August 2019) - Kino, Shiho; Jang, Soong-nang; Gero, Krisztina; Kato, Soichiro; Kawachi, Ichiro
Abstract: Japan and South Korea have among the highest suicide rates in the world. However, the age, gender, and time trends in each country differ substantially. Age-Period-Cohort (APC) analysis of suicide rates was conducted to better understand these differences. Using age- and gender-specific data on suicide between 1986 and 2015 in Japan and Korea, we implemented APC analysis to decompose the country-specific trends into age, calendar period, and birth cohort effects. APC analysis revealed three trends: (1) there was a sharp increase in suicide around retirement age in Korea but not in Japan (age effect); (2) there was a dramatic increase in suicide during the three decades of observation in Korea (period effect) whereas rates were more stable in Japan; and (3) the post-War generation in Japan (including baby boomer) had lower rates of suicide compared to generations born before 1916 or after 1961 (birth cohort effect), whereas suicide rate has increased linearly in each generation in Korea. Although Japan & Korea share high suicide rates, our APC analysis suggests divergent causes underlying these trends. Japanese suicide rates plateaued among the cohorts who experienced the post-War rapid economic growth (women born in 1951-1956 and men born in 1916-1961) (birth cohort effect) due to a strong social safety net for this cohort, while suicide rates in Korea continue to rise with each generation and is particularly elevated in post-retirement age. Japan and Korea need to pay more attention to suicide prevention in more recent birth cohorts. Highlights: Age, period, and cohort effects of suicide were unique in each country. In Japan, the post-war generation was relatively protected from suicide. In Korea, entering old age is the peak time for suicide risk during the life course. Cohort effect shows sharp rise in suicide rates of the younger generations.